Neuroprotective Drugs in Infants With Severe Congenital Heart Disease: A Systematic Review - Stegeman, Raymond; Lamur, Kaya D.; van den Hoogen, Agnes; Breur, Johannes M. P. J.; Groenendaal, Floris; Jansen, Nicolaas J. G.; Benders, Manon J. N. L. (Frontiers in Neurology, 2018)
Background: Perinatal and perioperative brain injury is a fundamental problem in infants with severe congenital heart disease undergoing neonatal cardiac surgery with cardiopulmonary bypass. An impaired neuromotor and neurocognitive development is encountered and associated with a reduction in quality of life. New neuroprotective drugs during surgery are described to reduce brain injury and improve neurodevelopmental outcome. Therefore, our aim was to provide a systematic review and best-evidence synthesis on the effects of neuroprotective drugs on brain injury and neurodevelopmental outcome in congenital heart disease infants requiring cardiac surgery with cardiopulmonary bypass. Methods: A systematic search was performed in PubMed, Embase and the Cochrane Library (PRISMA statement). Search terms were “infants,” “congenital heart disease,” “cardiac surgery,” “cardiopulmonary bypass,” and “neuroprotective drug.” Data describing the effects on brain injury and neurodevelopmental outcome were extracted. Study quality was assessed with the Cochrane Risk of Bias Tool. Two reviewers independently screened sources, extracted data and scored bias. Disagreements were resolved by involving a third researcher. Results: The search identified 293 studies of which 6 were included. In total 527 patients with various congenital heart diseases participated with an average of 88 infants (13–318) per study. Allopurinol, sodium nitroprusside, erythropoietin, ketamine, dextromethorphan and phentolamine were administered around cardiac surgery with cardiopulmonary bypass. Allopurinol showed less seizures, coma, death and cardiac events in hypoplastic left heart syndrome (HLHS) infants (OR: 0.44; 95%-CI:0.21–0.91). Sodium nitroprusside resulted in lower post cardiopulmonary bypass levels of S100ß in infants with transposition of the great arteries after 24 (p < 0.01) and 48 (p = 0.04) h of treatment. Erytropoietin, ketamine and dextromethorphan showed no neuroprotective effects. Phentolamine led to higher S100ß-levels and cerebrovascular resistance after rewarming and at the end of surgery (both p < 0.01). Risk of bias varied between studies, including low (sodium nitroprusside, phentolamine), moderate (ketamine, dextromethorphan), and high (erytropoietin, allopurinol) quality. Conclusions: Allopurinol seems promising for future trials in congenital heart disease infants to reduce brain injury given the early neuroprotective effects in hypoplastic left heart syndrome infants. Larger well-designed trials are needed to assess the neuroprotective effects of sodium nitroprusside, erytropoietin, ketamine and dextromethorphan. Future neuroprotective studies in congenital heart disease infants should not only focus on the perioperative period, however also on the perinatal period, since significant brain injury already exists before surgery.